Diversification of Financing Portfolio Through Gold Installment Products at PT BPRS Lantabur Tebuireng: Gold Installment - Lailatul Maghfiroh Putri Rifardi; Susi Noviana; Indah Raissa Qur’ani (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study examines portfolio diversification through gold installment products at PT BPRS Lantabur Tebuireng as a strategy for mitigating Non-Performing Financing (NPF) risk. Gold installment products use murabahah contracts, which allow customers to gradually acquire gold through a fixed installment system. The purpose of this study is to analyze the implementation of gold installment products as a financing diversification instrument and identify their role in mitigating NPF risk at PT BPRS Lantabur Tebuireng. The research method used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation studies. The results show that the gold installment product contributes significantly to NPF risk mitigation through collateral in the form of gold, which has stable value and high liquidity. Portfolio diversification through this product reduces the risk of financing concentration, which was previously dominated by conventional murabahah financing in the consumptive and productive sectors. The implementation of murabahah contracts in gold installment products is in accordance with sharia principles based on the DSN-MUI fatwa with price transparency and margin certainty. The study recommends optimizing gold installment products as a risk management strategy, strengthening the financing monitoring system, and developing similar products to strengthen the resilience of BPRS financing portfolios.